Research of Biochemical Composition and Antioxidant Activity of Freeze-dried Cranberry Powder Obtained on the Basis of Enzymatically Processed Berry Pulp - Alekseenko, E. V. (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: An important indicator of the quality of fruit and berry powder products, which determines the suitability of their use in the preparation of food products, is the chemical composition. Complex studies were conducted to study the chemical composition and antioxidant activity (AOA) of the freeze-dried cranberry berries obtained from the pulp of berries pre-treated with a piece of enzymatic preparations of pectolytic and cellulolytic action (Rapidase CR and Laminex BG2). The profile of flavonoids, qualitative composition of organic including phenolic acids, catechins, and minerals, has been studied. Results and Discussion: In the flavonoids, quercetin and its glycosides have been identified: Quercitrin, hyperoside, and avicularyin. Among the catechin compounds, epicatechin (more than 65%) is detected in the most considerable amounts; the epigallocatechin (about 18%) is the second in the quantitative series of catechins. Gallates are present in smaller amounts: Epicatechin gallate, gallocatechin gallate, and epigallocatechin gallate with a predominance of the latter (9%). In the composition of fruit acids, citric acid is present in the most significant amounts, and in the spectrum of hydroxycinnamic acids, chlorogenic acid (~45%) and 4-caffeolic acid (~22%) predominate; ferulic, coffee, p-coumaric, and caftaric acids have also been identified. A diverse range of mineral substances has been defined: Potassium, phosphorus, and calcium are leading, substantially magnesium content. From trace elements in significant quantities, there are manganese, iron, aluminum, silicon, and zinc. The high AOA of the sublimed cranberry berries powder is established. Conclusion: The obtained data convincingly demonstrate that the berry powder contains a wide range of natural biologically active and minor components useful for human health: Sugars, organic acids including natural preservative - benzoic acid, dietary fibers, protein, minerals, and Vitamin C, and polyphenolic compounds including flavones, flavonols, anthocyanins, catechins, proanthocyanidins, and tannins, as well as natural dyes and preservatives, which opens the prospect of using a freeze-dried powder berries cranberries in the preparation of foods and functional foods and therapeutic and prophylactic purposes.